Chemical constituents and biological activities of Glycosmis macrantha merr. and Cratoxylum arborescens (vahl) blume - Yahayu, Maizatulakmal (2012)
Phytochemical and biological activity studies of Glycosmis macrantha (family Rutaceae) and Cratoxylum arborescens (family Guttiferae) were carried out. The stem barks of Glycosmis macrantha and Cratoxylum arborescens were collected from Sabah and Sarawak, respectively. These two species were subjected to detail phytochemical investigation which involved extraction using three organic solvents of different polarity and isolation of the compounds by using common chromatographic techniques such as gravity column chromatography, vacuum column chromatography, chromatotron, preparative thin layer chromatography and gel filtration column chromatography using Sephadex LH20. The structural elucidations of the isolated compounds were carried out using spectroscopic techniques such as NMR, MS, IR, UV and by comparison with literature data. The phytochemical investigations have led to the isolation of several compounds of different classes including alkaloids, xanthones, flavonoids and triterpenoids. The crude extracts and some of the isolated compounds were tested for antioxidant, cytotoxic and antimicrobial activity using DPPH, MTT and disc diffusion methods, respectively. The cell line used in cytotoxic assay was the human breast cancer (MCF7) cell line. The antimicrobial activity was tested against eight microbes namely Bacillus subtilis, Bacillus cereus, Escherichia coli, Klebsiella pneumonia, Salmonella typhimurium, Staphylococcus aureus, Enterobacter aerogenes and Candida albican. The phytochemical study of Glycosmis macrantha has led to the isolation of two new acridone alkaloids, macranthanine (116), 7-hydroxynoracronycine (117); one known acridone alkaloid, namely atalaphyllidine (118), two flavonoids, dihydroglychalcone A (32) and epicatechin (58); and a sterol, β-sitosterol (119). Similar isolation work on Cratoxylum arborescens has yielded three xanthones, α-mangostin (36), β-mangostin (37) and fuscaxanthone C (103) together with stigmasterol (120). Among the pure compounds, only macranthanine (116) and 7-hydroxynoraconycine (117) exhibited significant activities towards antioxidant assay with IC50 values 63.3 and 80.2 μg/ml, respectively. The study on antiproliferative activity against human breast cancer (MCF7) cell line displayed that α-mangostin (36) and β-mangostin (37) exhibited significant activity with IC50 values of 12.48 μg/ml and 28.42 μg/ml respectively. Meanwhile, only α-mangostin (36) exhibited strong inhibition on the growth of B. subtilis, B. cereus, S. typhimurium and S. aureus with inhibition zone 16, 20, 17 and 20 mm, respectively.